Towards Energy and Performance-aware Geographic Routing for IoT-enabled Sensor Networks. (July 2020) - Hameed, Ahmad Raza; Islam, Saif ul; Raza, Mohsin; Khattak, Hasan Ali
Abstract: Internet of Things has been a pivotal technology enabler for realizing smart cities vision through the provision of connectivity for everyday objects by means of wireless sensor networks (WSNs). Scalability, flexibility, route efficiency, mobility support and reduced overhead in routing protocols are desired functions in large-scale WSNs. Given the several geographic routing schemes proposed, mainly focusing on positioning, location error, and energy consumption, still exhibit higher delays and overhead which significantly affect the performance of the network. In this paper, an energy-efficient geographic (EEG) routing protocol has been proposed that focuses on network throughput and energy consumption of sensor nodes. Moreover, this strategy also helps in avoiding void region's creation in the network. The proposed protocol reduces the energy hole problem by efficiently balancing the energy consumption among sensor nodes. The extensive simulations illustrate that the proposed scheme manages energy consumption and packet delivery ratio more efficiently in comparison to a state-of-the-art geographic routing protocol.